Factors of working environment on employees performance in oil palm plantation at RISDA Palong Estate, Negeri Sembilan Darul Khusus / Nurul Syafiqah Ramli - Ramli, Nurul Syafiqah (Faculty of Plantation and Agrotechnology, 2016)
A working environment will create a pleasant atmosphere within the organization to perform well. The relationship between working environment and employees performance of central interest to research in organizational psychology. This study aims to determine the performance of employees in Risda Palong Estates and to analyse the relationship between the factor of working environment and employees performance. A number of 88 respondent was interviewed from the company Risda Palong Estates of Risda Plantation Sdn. Bhd. Several analysis are used to measure up the reliability of the questionnaire and also normality analysis are used to measure up the normal distribution of each data. Correlation analysis are also used to measure up the strength of independent variable and the dependent variable of the study. The independent variable includes job satisfaction, company policy, salary and responsiveness of working environment. The dependent variable is the performance of the employees. Regression analysis are also used to measure up in which of the independent variable mostly influence the dependent variable. The result reveals that the working environment factors have a significant effect on the performance of Risda Palong Estate. It is also indicated that employees were less satisfied by the factor company policy and salary.